Un discours juridique pour le fascisme. Politiques impériale et raciale au prisme des revues de droit - Silvia Falconieri (Clio@Themis)
Which was the implication of the Italian lawyers in the policy of Ventennio? Did they adhere to the principles of fascism? Did they take part in the construction of a legal theory of fascism? Through a reading of the periodic legal press, this article proposes an analysis of the attitude of the Italian lawyers with respect to fascism by referring to colonial and racial policies. They are two burning subjects which, starting from the end of 1930, become the heart of action and the propaganda of the government. In the speech of the lawyers supporting the racial policy, colonialism and racism meet in the shaping of different statutes, founded on the ethnic criterion. The power of the legal speech built for fascism lies in this meeting between the two broad topics of the race and the Empire.